2022
DOI: 10.37394/232015.2022.18.75
|View full text |Cite
|
Sign up to set email alerts
|

Applied Research of Digital Readiness of Retails

Abstract: The paper contains a proposed methodology for determining the digital readiness of retail, which, unlike the known ones, allows managing the internal capabilities of digital transformation of enterprises in the FMCG retail segment. This technique has a number of advantages: data availability; ease of calculation; sufficiency and non-overloading of the attributes of the resulting feature; the possibility of using both in the process of primary self-diagnosis and at the control stage to determine the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
0
0
2
Order By: Relevance
“…Джерело: проаналізовано та узагальнено авторами на підставі [6,9] Означені групи трактування сутності дефініції «маркетингові комунікації» в контексті впливу трансформаційних економічних видозмін у залежності від підходу, що використовується допомагають класифікувати отримані результати та оцінювати можливі перспективи стратегічних перетворень. Подальші наукові дослідження будуть направлені на створення узагальненої комплексної моделі управління маркетинговими комунікаціями на ринку нерухомості у середньо-та довгостроковій перспективах.…”
Section: взаємозалежнаunclassified
“…Джерело: проаналізовано та узагальнено авторами на підставі [6,9] Означені групи трактування сутності дефініції «маркетингові комунікації» в контексті впливу трансформаційних економічних видозмін у залежності від підходу, що використовується допомагають класифікувати отримані результати та оцінювати можливі перспективи стратегічних перетворень. Подальші наукові дослідження будуть направлені на створення узагальненої комплексної моделі управління маркетинговими комунікаціями на ринку нерухомості у середньо-та довгостроковій перспективах.…”
Section: взаємозалежнаunclassified
“…This theory emphasizes how the interaction between tasks, people, structure, and technology impacts efficiency, productivity, and quality of work. Sociotechnical systems theory has been applied in industry 4.0 or digital transformation research in the family business context (Pradana et al, 2022;Savytska et al, 2022;Sony & Naik, 2020).…”
Section: Sociotechnical Systems Theorymentioning
confidence: 99%
“…Sociotechnical systems theory has been applied to assess an organization's digital maturity and transformation in the FMCG retail segment (Savytska et al, 2022). The researchers found that unmotivated managers, digital mindset, limited digitalization experience, limited financial capability, limited digital skill, and lack of evaluation will slow down the digitalization process.…”
Section: Sociotechnical Systems Theorymentioning
confidence: 99%
“…Розвитку прикладного інструментарію аналітичного маркетингу для вирішення певних управлінських завдань приділено у попередніх роботах автора [1], [4], а також у наукових працях вітчизняних учених, серед яких О.…”
unclassified